2023
DOI: 10.1038/s41467-023-38264-4
|View full text |Cite
|
Sign up to set email alerts
|

Central medial thalamic nucleus dynamically participates in acute itch sensation and chronic itch-induced anxiety-like behavior in male mice

Abstract: Itch is an annoying sensation consisting of both sensory and emotional components. It is known to involve the parabrachial nucleus (PBN), but the following transmission nodes remain elusive. The present study identified that the PBN-central medial thalamic nucleus (CM)-medial prefrontal cortex (mPFC) pathway is essential for itch signal transmission at the supraspinal level in male mice. Chemogenetic inhibition of the CM-mPFC pathway attenuates scratching behavior or chronic itch-related affective responses. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 58 publications
0
1
0
Order By: Relevance
“…Thus, a multi-synaptic neural circuit between the spinal cord, PBN, and RVM is instrumental in driving and modulating pain thresholds and simultaneously suppressing itch-induced scratching. The PBN Tacr1 neurons project to the central thalamus and may mediate the affective-motivational components of itch through this connection (Li et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a multi-synaptic neural circuit between the spinal cord, PBN, and RVM is instrumental in driving and modulating pain thresholds and simultaneously suppressing itch-induced scratching. The PBN Tacr1 neurons project to the central thalamus and may mediate the affective-motivational components of itch through this connection (Li et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescence in situ hybridization (FISH) staining was performed according to the procedures described in previous studies [23]. Tac1-Ai9 mice were perfused and sectioned with enzymes-free throughout the experiments.…”
Section: Fluorescence In Situ Hybridizationmentioning
confidence: 99%
“…The parabrachial nucleus (PBN), being located within the pons, functions as an integrator of sensory input from the surrounding environment and subsequently relays this information to forebrain structures. The majority of PBN neurons are Ivyspring International Publisher excitatory features [4,5], being positively correlated with behaviors indicative of pain [6][7][8], itch [9,10], fear [11], aversive [12], and emotion [10,13]. Our recent research has identified a specific subpopulation of choline acetyltransferase (ChAT + ) neurons located in the PBN, specifically within the external lateral portion of PBN (eLPB ChAT ) [14].…”
Section: Introductionmentioning
confidence: 99%